Progress of long-chain noncoding small nucleolar RNA host genes in thyroid cancer - Yang, Tingyu; Xie, Yuanxu (Frontiers in Oncology, 2025)
Small nucleolar RNA host genes (SNHGs) are a class of long non-coding RNAs that are widely aberrantly expressed in thyroid cancer and regulate tumor progression through the “SNHG–miRNA–signaling pathway” network. SNHG7 promotes cell proliferation and metastasis via the PI3K/Akt pathway and correlates with radioactive iodine resistance; SNHG15 accelerates epithelial-mesenchymal transition via the Hippo-YAP1 pathway; SNHG12 drives malignant phenotypes by interacting with Wnt/β-catenin signaling; SNHG14 enhances tumor invasion through multiple miRNA axes. In contrast, SNHG3 and SNHG5 exhibit tumor-suppressive effects in some studies. Overall, SNHGs may serve as molecular biomarkers and hold potential therapeutic target value. However, existing evidence is largely based on in vitro and small-sample studies, requiring further validation in clinical cohorts and functional models.